Problem Mechanism and Solution Strategy of Rural Children’s Community Inclusion—The Role of Peer Environment and Parental Community Participation - Xu, Ying; Wang, Ligang; Yang, Wanyi; Cai, Yi; Gao, Wenbin; Tao, Ting; Fan, Chunlei (Frontiers in Psychology, 2022)
Early childhood development intervention has gained considerable achievements in eliminating intergenerational transmission of poverty in rural areas. Paying further attention to rural children’s community inclusion can also promote the sustainable development of the village. However, there is a lack of systematic theoretical constructs on the village inclusion of rural children. In this study, an attempt was made to explore the problem mechanism and solution strategy of community inclusion of rural children using a grounded theory approach of in-depth interviews. Fifteen parents of children in a national-level poverty-stricken county in Inner Mongolia were investigated, adopting the strategy of intensity sampling. The results revealed that (1) the content of rural children's activities demonstrates enhanced participation in the virtual environment and weakened participation in the real community environment. That is, the activities are characterized by more virtualization and individualization. (2) Rural parents and community peers are two major channels for children's community inclusion, while both the community peer environment and parental community participation show a weakening trend. This may be an important reason for the virtualization and individualization of the children’s psychological development environment. (3) Developmental intervention programs for rural children in poverty-stricken areas should focus on the reconstruction of children's community peer environment, encourage the community participation of parents, and fully mobilize local-based educational resources.